Group A Streptococcal Toxic Shock Syndrome Developing in the Third Trimester of Pregnancy - Nancy F. Crum; Helen M. Chun; Thomas G. Gaylord; Braden R. Hale (Hindawi Limited, 2002)
Background: Group A streptococcal (GAS) toxic shock syndrome (TSS) is an uncommon, but life-threatening infection during pregnancy and should be considered in rapid onset of shock.Most cases described in the literature have occurred in the puerperium.We report a case of GAS TSS occurring during the third trimester of pregnancy in a previously healthy woman.